Emerging technologies for economic development - Dirk Meissner, Leonid Gokhberg, Ozcan Saritas, editors (Switzerland: Springer International Publishing, 2019)
This book provides an impressive overview of emerging technologies, especially nanotechnologies and biotechnologies, and their prospective applications. It identifies and describes existing and potential markets for emerging technology-based applications, and projects scenarios for macroeconomic development based on these technologies. Integrated roadmaps for the development of a nano- and bioindustry are shown and policy measures and corporate strategies developed to advance these technologies. These measures are illustrated using roadmaps and policy case studies.The book combines a practical, comprehensive overview of the technical side of emerging technologies and their applications in various fields with an analysis of market developments and characteristics.
Keywords: Economic development--Technological innovations